Correction of endothelial dysfunction among patients suffering from diabetes mellitus - I. V. Savitsky; V. N. Sarakhan; I. V. Miastkivska; V. I. Savitsky (Kazimierz Wielki University, 2017)
The number of patients with diabetes mellitus (DM) according to WHO is constantly increasing. At the same time, it is known that one of the main pathogenetic links of diabetes is excessive activation of processes of free radical oxidation. Literary sources indicate that phenolic compounds are effectively acting as synergists and regulators of the antioxidant system, the most numerous of which are flavonoids, including anthocyanins. A number of researchers distinguish flavonoids as promising endothelioprotectors under different pathological conditions. Goal: to investigate the dynamics of the content of markers of endothelial dysfunction among patients with diabetes mellitus correcting the pro- and antioxidant system with the help of flavonoids. Materials and methods. The study involved 40 patients with type 2 diabetes at the age of 40 to 60 years. To study the effectiveness of flavonoids under these conditions, we chose the drug "GEMOGLOBIN NECTAR PLUS". The first stage of the study was the determination of Willebrand factor and endothelin-1 in the blood serum before the flavonoids were taken. The second stage of the study was the determination of the test markers of endothelial dysfunction 2 months after the start of the regular intake of the drug anthocyanins, which are known as flavonoids. As a result of our study, the following data were obtained: The relationship between pro and antioxidant system disorders and endothelial dysfunction among patients with diabetes mellitus was confirmed. The normalization of Willebrand factor among patients taking flavonoids according to data obtained before the use of the drug was proved. There was a change in the vaconstrictor-vasodilatation potential under the action of the anthocyanin concentrate directing to the reducing of pathological vasoconstriction and, consequently, normalization of blood supply processes. The drug "GEMOGLOBIN NECTAR PLUS", being a powerful antioxidant, significantly improves the functional state of the endothelium.